1997
DOI: 10.1098/rspb.1997.0251
|View full text |Cite
|
Sign up to set email alerts
|

Xylem colonization of the legume Sesbania rostrata by Azorhizobium caulinodans

Abstract: A novel pathway of invasion of the legume Sesbania rostrata by Azorhizobium caulinodans is described that involves colonization of the root xylem, possibly following entry into the natural ¢ssures created during emergence of lateral roots. Azorhizobia were detected microscopically, and their presence con¢rmed by the expression of a lacZ reporter gene. We have shown that rhizobial Nod factors are not required for either xylem colonization or for crack-entry of lateral roots. We discuss the extent to which this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The fact that the internal colonisation and crack entry of wheat and rice (and Arabidopsis) are not under the control of the usual nod genes suggests that nitrogen fixation is more likely to be endosymbiotic than nodular (Gough et al 1996). The opportunity now exists to carry out a similar investigation in wheat since Azorhizobium caulinodans has been isolated from short lateral roots of wheat and shown to re-invade wheat (by crack entry) and also when nodulating its legume host, Sesbania rostrata (O'Callaghan et al 1997). Labelling studies have also shown clear evidence of substantial xylem colonisation in the case of oilseed rape (O'Callaghan et al 2000), raising the question of the extent to which xylem flow may be impeded.…”
Section: Modified and Engineered Systemsmentioning
confidence: 99%
“…The fact that the internal colonisation and crack entry of wheat and rice (and Arabidopsis) are not under the control of the usual nod genes suggests that nitrogen fixation is more likely to be endosymbiotic than nodular (Gough et al 1996). The opportunity now exists to carry out a similar investigation in wheat since Azorhizobium caulinodans has been isolated from short lateral roots of wheat and shown to re-invade wheat (by crack entry) and also when nodulating its legume host, Sesbania rostrata (O'Callaghan et al 1997). Labelling studies have also shown clear evidence of substantial xylem colonisation in the case of oilseed rape (O'Callaghan et al 2000), raising the question of the extent to which xylem flow may be impeded.…”
Section: Modified and Engineered Systemsmentioning
confidence: 99%
“…phaseoli, trifolii and viceae (Chabot et al 1996;Yanni et al 1997;Chi et al 2000, Matiru andDakora, 2004), Rhizobium sp. (Alami et al 2000;Gutiérrez-Zamora and Martibez-Romero, 2001;Afzal and Bano, 2008), Bradyrhizobium japonicum (Matiru and Dakora, 2004), photosynthetic bradyrhizobia (Chaintreuil et al 2000), Sinorhizobium meliloti (Matiru and Dakora, 2004), Azorhizobium caulinodans (Gough et al 1996;O'Callaghan et al 1997;Chi et al 2000) and Burkholderia brasilensis (Baldani et al 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is now clear that the energy required for the reduction of nitrogen to ammonia in nitrogen fixation is no greater than that required for the production of ammonia by the reduction of nitrate, the main form of nitrogen assimilated by plants. 12 The discovery that Azorhizobium is able to colonize the xylem of its legume host 13 , and non-legumes such as wheat 14 and rice 15 , has provided an important parallel with the internal colonization of sugarcane by diazotrophic bacteria. Experiments are being undertaken to inoculate cereals and other non-legume crops with Acetobacter and with Azorhizobium to try to establish these diazotrophs within the crop plant to investigate the extent to which they will fix nitrogen of benefit to growth and development.…”
Section: Expectationsmentioning
confidence: 99%